Implantation and preliminary follow‐up of the Bard Valeo stent in pulmonary artery stenosis. Issue 2 (27th February 2014) - Kudumula, Vikram; Noonan, Patrick; Taliotis, Demetris; Duke, Christopher
<x xml:space="preserve">Abstract</x> Objectives To evaluate the performance of the Bard Valeo stent in pulmonary artery stenoses. Background The premounted Valeo stent requires only 6–7 French access and can be post‐dilated to 20 mm on bench testing. Although it appears ideal for implantation in pulmonary artery stenoses in children, it has been unclear whether it has sufficient radial strength to prevent vessel recoil and stent collapse. Methods Twelve stents were implanted in 10 patients aged 1.2–19.9 years (weight 9.9–54 kg). Implant results were assessed retrospectively. Results All implants were successful with no complications. The stent tracked easily and was readily visible on fluoroscopy. The median (range) diameter of the pulmonary artery stenosis increased from 4.9 (1.8–7.4) mm to 9 (6–10.6) mm (P ≤ 0.01), the median peak to peak systolic pressure gradient across the pulmonary artery stenosis decreased from 16 (11–66) mmHg to 6 (0–10) mmHg (P ≤ 0.01), and the right ventricle to systemic blood pressure ratio fell from 0.72 (0.54–1.1) to 0.54 (0.28–0.69) (P ≤ 0.01). Median stent recoil was 5.5 (0–21)%. Jailed side branches remained patent. Nine stents were assessed fluoroscopically on 11.5 (0–30) month follow‐up. There were no stent fractures. 6 stents were not distorted, 2 had minor distortion, and 1 stent, implanted in a highly resistant lesion, had moderate distortion. Conclusions The Valeo stent is low profile, conformable, and easy to deliver, even in small children. It has adequate radial strength to stent pulmonary artery stenoses with minimal recoil. It maintains its geometry on medium term follow up in compliant lesions. Resistant stenoses may distort the stent. © 2014 Wiley Periodicals, Inc.